Neuroscience In Islamic Religious Education Learning - Anis Luthfiyani; Ferdian, Ferdian; Sutarto; Ermis Suryana; Suhono, Suhono (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
In the world of education, many discoveries state that humans have not maximized in using the potential of their brains, such as creating new ideas or solving problems. So, this study aims to describe and analyse the relevance of neuroscience in PAI learning and what role neuroscience plays in PAI learning. The methodology applied to this research is a descriptive qualitative method approach, and this research is a type of library research, which is a research based on the source of books, papers, articles, journals and other scientific works that support this research. The results of this study show that neuroscience has a close relationship with PAI learning, where in the implementation of learning neuroscience is needed so that learning can run smoothly and effectively, where neuroscience can help PAI teachers understand better how students’ brains process information and learning materials so that teachers can develop varied teaching strategies and come up with the latest innovations in learning. Neuroscience plays an active role in PAI learning to improve students’ cognitive development.